Menelusuri Jejak Teori Generatif-Transformatif: Dari Pokok Pikiran Hingga Uji Coba Lapangan - Anjani Rohmatul Ummah; Rahma Sekarningrum; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The generative-transformational theory, pioneered by Noam Chomsky, posits that humans possess an innate linguistic capability, enabling the construction of an infinite number of sentences through systematic grammatical rules. Central to this theory are the concepts of deep and surface structures, highlighting the creative nature of language use. Its development has been influenced by key figures: Zellig Harris, who initiated transformational analysis; Roman Jakobson and Morris Halle, who advanced generative phonology; Eric Lenneberg, who emphasized the biological aspects and critical period of language acquisition; Jean Berko Gleason, whose